Early Chest CT Manifestations and Temporal Evolution in COVID-19 Pneumonia: A Retrospective Cohort Study from Wuhan, China - Xian Li; Lin Chia (Sriwijaya Journal of Radiology and Imaging Research, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) is a global pandemic with a wide spectrum of clinical manifestations, ranging from asymptomatic infection to severe pneumonia and acute respiratory distress syndrome (ARDS). Chest computed tomography (CT) plays a crucial role in the diagnosis and management of COVID-19 pneumonia. This study aimed to investigate the early chest CT manifestations and temporal evolution of COVID-19 pneumonia in a cohort of patients from Wuhan, China, the epicenter of the initial outbreak. Methods: This retrospective cohort study included 100 consecutive adult patients with laboratory-confirmed COVID-19 pneumonia admitted to a designated hospital in Wuhan, China, between December 2019 and February 2020. All patients underwent serial chest CT scans during their hospitalization. Two experienced radiologists independently reviewed the CT images and recorded the imaging findings, including the distribution, morphology, and extent of lung opacities, as well as other associated features. The temporal evolution of the CT findings was also analyzed. Results: The most common early chest CT manifestations of COVID-19 pneumonia were ground-glass opacities (GGOs) (98%), followed by consolidation (65%), and crazy-paving pattern (32%). The lesions were predominantly distributed in the peripheral and subpleural regions of the lungs, with bilateral and multilobar involvement in most cases. The extent of lung involvement progressed rapidly in the first week after symptom onset, reaching a peak around day 10, and then gradually improving in the following weeks. Other associated CT findings included air bronchograms, vascular enlargement, pleural thickening, and lymphadenopathy. Conclusion: Early chest CT manifestations of COVID-19 pneumonia are characterized by GGOs, consolidation, and crazy-paving patterns, with a predominant peripheral and subpleural distribution. The extent of lung involvement progresses rapidly in the first week and peaks around day 10. Chest CT is a valuable tool for the early diagnosis and monitoring of COVID-19 pneumonia.